On interdisciplinarity and non-disciplinary research: a conversation - Pizzo, Barbara; Rolnik, Raquel (Tracce urbane. Rivista italiana transdisciplinare di studi urbani, 2019)
Barbara Pizzo in conversation with Raquel Rolnik. Aim of this special issue of Tracce Urbane is to critically explore the issue of interdisciplinarity for Planning and Urban Studies. To practice forms of interdisciplinarity is a fundamental goal of the research group which launched this journal, and the journal itself was born to cross and overcome disciplinary boundaries, thus the necessity arises to explicit discuss this issue.